Mellin Transform of Dirichlet L-Functions with Primitive Character - Balčiūnas, Aidas; Šiaučiūnas, Darius (Mathematical Modelling and Analysis, 2014)
In the paper, meromorphic continuation for the modified Mellin transform of Dirichlet L-functions with primitive character is obtained.